Pushing the creolisation paradigm on the Comorian island of Ngazidja: when does creolisation cease to be? - Walker, I (International Migration Institute, 2013)
What is 'creolisation’, and at what point do processes that might be called 'creolisation’ no longer warrant the name? At what point do creole societies cease to be 'creole’? Creolisation, in the Hannerzian sense of the word, conjures up images of hybridity, globalisation, cosmopolitanism; while not a uniquely contemporary phenomenon it is nevertheless widely associated with the political and economic expansion of the European world, and the cultural implications thereof, in the colonial and post-colonial eras. On the Comorian island of Ngazidja in the western Indian Ocean, processes of social change have been the product of interactions with the outside world since first settlement of the islands some two millennia ago. Much as in neighbouring Mauritius or Réunion, but on a longer timescale, waves of immigrants have arrived on the island, interacting with the inhabitants, each other, and their external partners. They have constituted Ngazidja society and culture as 'hybrid’, through processes of interaction that today—and they continue today—would be called 'creolisation’. This paper considers whether the term 'creolisation’ is an appropriate and useful description of these processes or whether the widening of the term to such long-term (and perhaps less visible) processes diminishes its acuity.